Potential of acmeology and acmeologic approach in the organization of rehabilitation activities of the servicemen the combatants by the social services’s speciaists - Бриндіков, Ю. Л. (Scientific notes of the pedagogical department, 2018)
The experience gained during the fighting has a negative impact on the combatants. As a result, after returning to a peaceful life, they often can not adapt to a peaceful life, they are not always understood by their relatives, they also have difficulty communicating, it is difficult to self-actualize and there are conflicts in their families. Often the combatants themselves can not cope with these changes, therefore they need qualified assistance, which involves the organization of rehabilitation activities. It is considered in the article the essence of rehabilitation as a scientific category in pedagogical literature. As practice shows, servicemen the combatants require increased social attention and organization of the system of complex rehabilitation from the social services’ specialists. It is substantiated that the methodological basis of acmeology provides opportunities for qualitative organization of rehabilitation activities with the combatants, and the acmeological approach is one of the most promising, which allows transferring rehabilitation activities from the regime of simple functioning in social services to the mode of creative development. The main focus is on highlighting the essence and characterization of specific practical models based on the acmeological approach. In particular, there are outlined the content is analyzed and the practical aspects of such practical models as life skills training, motivation, affective learning, coping behavior, self-efficacy and social support. The use of practical models will help to intensify the internal capabilities of the combatant and facilitate the use of all resources. On their basis, the combatant will be able to restore his status in the process of adaptation to the conditions of peace after the effects of military conflict. A social specialist, mastering in his practical activity, innovations based on the acmeological approach is an innovator free from stereotypes. The acmeological approach contributes to the formation of a high level of moral duty and responsibility to each participant in military operations, who sought rehabilitation assistance in social services.